2013
DOI: 10.1080/13614533.2013.800754
|View full text |Cite
|
Sign up to set email alerts
|

Student Journey Work: A Review of Academic Library Contributions to Student Transition and Success

Abstract: Student Journey Work: the contribution of academic libraries to student transition and success -a review Scope and IntroductionThis review identifies and draws on accounts of recent practice (published within the last threefour years) which describe library innovations taking place nationally and internationally. Rather than an in-depth review the article identifies and explores notable examples of projects, services, and approaches that are extending the traditional function of the academic library. Consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Student retention is vital and lack of skills is often cited as a reason for dropout (HERE Project 2011;Emmons and Wilkinson 2011;Weaver 2013). As the library needs to justify its role in regards to user satisfaction surveys and students receiving value for money, this trend needs addressing.…”
Section: The Need To Engagementioning
confidence: 98%
“…Student retention is vital and lack of skills is often cited as a reason for dropout (HERE Project 2011;Emmons and Wilkinson 2011;Weaver 2013). As the library needs to justify its role in regards to user satisfaction surveys and students receiving value for money, this trend needs addressing.…”
Section: The Need To Engagementioning
confidence: 98%
“…A strong focus on outcomes is reflected in the term student success which is commonly central to the institutional mission and linked to student expectations of employability (Adams Becker et al, 2017a). Higher student fees have promoted the view of students not only as customers (Weaver, 2013) but also as partners, with a stronger voice in decision-making (Melling, 2013). There is an increased focus on the student experience (Appleton et al, 2011), and greater scrutiny of the quality and value for money of services (Melling & Weaver, 2017).…”
Section: Theme 3 Positioning For Student Successmentioning
confidence: 99%
“…Libraries now need to understand the entirety of the student experience from recruitment to graduate employment (Weaver, 2013). Progression incorporates retention, the subject of a literature review by Oliveira (2017) which includes a section titled "Retention is the library's business too" (p. 314).…”
Section: Influencing the Student Journeymentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by Karagiannopoulou (2006) and Christie et al (2016) who found in their studies that the students had increased their knowledge of academic writing, enhanced their critical skills and adopted a deep strategic approach. Weaver (2013) suggests that academic libraries also play an important part and role in the students' journey throughout their studies. Furthermore, Weaver (2013) makes the point that collaboration is necessary to teach the students the relevance of IL.…”
Section: )mentioning
confidence: 99%